2004
DOI: 10.1063/1.1766615
|View full text |Cite
|
Sign up to set email alerts
|

Optimized Tooling Design Algorithm for Sheet Metal Forming over Reconfigurable Compliant Tooling

Abstract: FE Robustness: comparing sheet metal forming variation and finite element models AIP Conf. Proc. 712, 958 (2004); Abstract. New forming technologies based on compliant "discrete-die" reconfigurable tooling are available for production of sheet metal parts, but there is a need for a formalism that can accurately predict the three-dimensional shape of the required tooling, a priori. An optimized tooling design algorithm has been developed based on a methodology that uncouples the effects due to springback and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 4 publications
0
21
0
Order By: Relevance
“…The amount of springback is highly coupled with the stress distribution in the formed part prior to unloading, the applied boundary condition and material deformation behavior. This problem can be corrected by adjusting the tooling shape to the appropriate shape, i.e., the "springforward" method 12,13,14,15,16 , and/or using active process control of external forces during the loading stage 17,18,19 .…”
Section: 34 Fea/fem -Stress-strain Modelingmentioning
confidence: 99%
“…The amount of springback is highly coupled with the stress distribution in the formed part prior to unloading, the applied boundary condition and material deformation behavior. This problem can be corrected by adjusting the tooling shape to the appropriate shape, i.e., the "springforward" method 12,13,14,15,16 , and/or using active process control of external forces during the loading stage 17,18,19 .…”
Section: 34 Fea/fem -Stress-strain Modelingmentioning
confidence: 99%
“…Using finite element analysis, Boyce and Anagnostou investigated the ability of a polymer pad to smooth out the local pressure and predicted the springback of an unloaded workpiece. Through experiment and simulation, it was discovered that the key variables in dimple suppression by polymeric pad were thickness and compressive modulus [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…This type of tooling is expensive to manufacture and is uneconomic for small batch quantities. For this reason, some flexible reconfigurable tool designs have been suggested such as the discrete die tool [1,2], the reconfigurable stretch forming tool [3][4][5] and rubber pad tool [6,7]. There tool design can be used to form a number of different part shapes and can be used economically for small batch quantity production.…”
Section: Introductionmentioning
confidence: 99%
“…After the 1980s, the concept of reconfigurable tooling for flexible fabrication was proposed by Hardt and Gossard [6]. In the previous of Nakajima and the others, a discrete die mechanical design was explored, which can rapidly fabricate sheet metal parts [5][6][7][8][9][10][11][12][13][14][15][16][17]. A shape control algorithm was proposed which based on the concept of the deformation transfer function, and it can be used to compensate for springback and other production variables [8,17].…”
Section: Introductionmentioning
confidence: 99%
“…MIT, Grumman Aerospace, and Cyril Bath Company developed a reconfigurable stretch forming die, which measures 1.83×1.20 m (6×4 ft) and consists of 2,688 pins, with 42 pins along one side and 64 along the other [13]. A survey analysis revealed that a single reconfigurable die could replace hundreds of fixed tools that are currently in use [15]. In MPF, plenty of studies and progresses were made in recent years [18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%